2020
DOI: 10.3389/fneur.2020.580910
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Newly Diagnosed Patients With Parkin-Related Parkinson's Disease

Abstract: Introduction: Mutations in the Parkin gene are the most common cause of autosomal recessive early-onset Parkinson's disease (PD). However, little is known about the quality of life (QoL) in Parkin-related PD. Here, we investigated the patterns of QoL in newly diagnosed Parkin-related PD patients.Methods: Newly diagnosed PD patients (diagnosis made within 12 months) who had an age of onset (AOO) below 40 and underwent a PD-related genetic testing, were recruited (n = 148). Among them, 24 patients carried bi-all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…1). Twelve studies were included to compare patients with and without heterozygous GBA carriers [5,[14][15][16][17][18][19][20][21][22][23][24], 17 studies to compare patients with and without heterozygous LRRK2 carriers [15,16,[20][21][22][25][26][27][28][29][30][31][32][33][34][35][36] and seven studies to compare patients with and without homozygous or compound heterozygous PRKN carriers [7,8,15,[37][38][39][40]. Six studies comparing asymptomatic heterozygous GBA carriers with non-carrier HCs were selected [9,10,20,[41][42][43], and 11 studies compared asymptomatic heterozygous LRRK2 carriers with non-carrier HCs [9, 20, 29-31, 42, 44-48].…”
Section: Characteristics Of the Selected Studiesmentioning
confidence: 99%
“…1). Twelve studies were included to compare patients with and without heterozygous GBA carriers [5,[14][15][16][17][18][19][20][21][22][23][24], 17 studies to compare patients with and without heterozygous LRRK2 carriers [15,16,[20][21][22][25][26][27][28][29][30][31][32][33][34][35][36] and seven studies to compare patients with and without homozygous or compound heterozygous PRKN carriers [7,8,15,[37][38][39][40]. Six studies comparing asymptomatic heterozygous GBA carriers with non-carrier HCs were selected [9,10,20,[41][42][43], and 11 studies compared asymptomatic heterozygous LRRK2 carriers with non-carrier HCs [9, 20, 29-31, 42, 44-48].…”
Section: Characteristics Of the Selected Studiesmentioning
confidence: 99%
“…It has been reported that monogenic PD patients with mutations in the α-synuclein, LRRK2, VPS35, Parkin, PINK1, DJ-1 and GBA genes exhibit psychiatric disturbances such as depression and anxiety (Liu et al 2020b ). In particular, PD patients carrying parkin, PINK1 and GBA mutations have more severe depression compared with idiopathic PD (Ephraty et al 2007 ; Thaler et al 2018 ; Zhou et al 2020 ). Currently, there are no guidelines or recommendations for selective treatment of depression associated with PD, so patients with PD are not receiving the optimal treatment for depression (Weintraub et al 2003 ).…”
Section: Depressionmentioning
confidence: 99%
“… The transcriptomic datasets generated are useful for identifying genes involved in the PD pathogenesis and determining mechanisms of PD onset associated with mutations in PARK2. PARK2 was selected for analysis as mutations in this gene have been shown to cause autosomal recessive early onset PD [2] , [3] . These data are valuable for researchers who investigate gene network in the process of neuronal differentiation and molecular mechanisms involved in PD development.…”
Section: Value Of the Datamentioning
confidence: 99%
“…The transcriptomic datasets generated are useful for identifying genes involved in the PD pathogenesis and determining mechanisms of PD onset associated with mutations in PARK2. PARK2 was selected for analysis as mutations in this gene have been shown to cause autosomal recessive early onset PD [2] , [3] .…”
Section: Value Of the Datamentioning
confidence: 99%